2021
DOI: 10.33423/jop.v21i3.4307
|View full text |Cite
|
Sign up to set email alerts
|

Dark Traits and Hacking Potential

Abstract: This paper investigates the psychological traits of individuals' attraction to engaging in hacking behaviors (both ethical and illegal/unethical) upon entering the workforce. A new set of scales have been developed to assist in the delineation of the three hat categories. We have also developed a scale to measure each subject's perception of the probability of being apprehended for violating privacy laws. The results suggest that white hat, grey hat, and black hat hackers score high on the Machiavellian and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…Although research is still emerging on the role of the Dark Triad in developing a hacker persona, some existing research indicates that some or all of the Dark Triad personality traits predict hacking intent or feelings about hacking. For example, a study involving 474 subjects found that white, grey, and black hat hackers scored high on the Machiavellian and psychopathy scales (Gaia 2021). Another recent study found relationships between the Dark Triad and techniques for hacking.…”
Section: Psychological Research On Hackersmentioning
confidence: 99%
“…Although research is still emerging on the role of the Dark Triad in developing a hacker persona, some existing research indicates that some or all of the Dark Triad personality traits predict hacking intent or feelings about hacking. For example, a study involving 474 subjects found that white, grey, and black hat hackers scored high on the Machiavellian and psychopathy scales (Gaia 2021). Another recent study found relationships between the Dark Triad and techniques for hacking.…”
Section: Psychological Research On Hackersmentioning
confidence: 99%